STREAMLINING ORGANIZATIONAL MANAGEABILITY THROUGH SCALABLE DECISION MAKING - NANTOI, Vadim; NANTOI, Daria (Journal of Social Sciences)
In modern organizations, decision-making processes are critical to effectively managing business operations. However, as organizations grow more complex, decision-making becomes more challenging and time-consuming, leading to a lack of agility, bottlenecks and decreased productivity. One of the assumptions in the article is that excessive complexity and uncontrolled secrecy in organizations lead to lack of understanding of how they work. This can be detrimental to decision-making processes, resulting in misinterpretations of data, misunderstandings of organizational objectives and ultimately, poor decision-making and results. These factors can create a wall of ignorance and irresponsibility within organizations. To address this issue, we propose the hypothesis that simplifying decision-making processes and making them more scalable and this will increase employee involvement and trust in the organization. Implementing scalable decision-making processes can create a framework for making consistent decisions across teams and departments, streamline the decision-making process, encourage critical thinking and enable the organization to respond more quickly and rationally to changing market conditions. The conclusion of the article is that applying scalable decision-making in organization can unlock new levels of manageability, improving the ability to make complex decisions and navigate dynamic situations. This model may be applicable to transportation and logistics companies, production units and plants and construction and manufacturing industries seeking to improve their performance and competitiveness in today's fast-paced business environment.